Tripartite networks show that keystone species can multitask - Timóteo, Sérgio (2023)
Keystone species are disproportionately important for ecosystem functioning. While all species engage in multiple interaction types with other species, keystone species importance is often defined based on a single dimension of their Eltonian niche, that is, one type of interaction (e.g. keystone predator). It remains unclear whether the importance of keystone species is unidimensional or if it extends across interaction types. We conducted a meta-analysis of tripartite interaction networks examining whether species importance in one dimension of their niche is mirrored in other niche dimensions, and whether this is associated with interaction outcome, intimacy or species richness. We show that keystone species importance is positively associated across multiple ecological niche dimensions, independently of abundance, and find no evidence that multidimensionality of keystone species is influenced by the explanatory variables. We propose that the role of keystone species extends across multiple ecological niche dimensions, with important implications for ecosystem resilience and conservation. Read the free Plain Language Summary for this article on the Journal blog.